2018
DOI: 10.1080/16070658.2018.1468536
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related knowledge, attitude and practices (KAP) of adult patients with type 2 diabetes mellitus in the Free State province, South Africa

Abstract: Type 2 diabetes mellitus (T2DM) is a global health problem with high morbidity and mortality in patients who are mostly still economically active. The growing incidence and health implications for those affected make T2DM a major public health issue. Objectives: To compile a demographic, anthropometric and knowledge, attitude and practices (KAP) profile of adult patients with T2DM in the public health sector of the Free State province, South Africa. Design: A descriptive observational study was conducted. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 20 publications
7
33
0
Order By: Relevance
“…Though this is not the typical gender pattern for T2DM reported in higher income countries, 12 it is consistent with the findings of other studies on T2DM in Lesotho [25][26][27] and neighbouring South Africa. [28][29][30] This may be explained by the fact that, in sub-Saharan Africa and other developing regions, the most prominent risk factor, which is obesity, is more common in women than in men, 12 as is also evident in the current study. The exact aetiology of this gender disparity is not fully understood, and has been attributed to a more significant impact of the nutrition transition on the physical activity levels of women, cultural views that favour female obesity, gender differences in carbohydrate metabolism that cause a more pronounced increase in triglyceride levels in women, as well as income disparities.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Though this is not the typical gender pattern for T2DM reported in higher income countries, 12 it is consistent with the findings of other studies on T2DM in Lesotho [25][26][27] and neighbouring South Africa. [28][29][30] This may be explained by the fact that, in sub-Saharan Africa and other developing regions, the most prominent risk factor, which is obesity, is more common in women than in men, 12 as is also evident in the current study. The exact aetiology of this gender disparity is not fully understood, and has been attributed to a more significant impact of the nutrition transition on the physical activity levels of women, cultural views that favour female obesity, gender differences in carbohydrate metabolism that cause a more pronounced increase in triglyceride levels in women, as well as income disparities.…”
Section: Discussionsupporting
confidence: 60%
“…Overall consumption of fruit, vegetables and dairy was below the recommendations for cardiometabolic health, 22 which concurs with the findings of a recent study among outpatients with T2DM attending public healthcare facilities in the five districts of the neighbouring Free State province of South Africa. 29 A large body of evidence supports the protective effects of fruit and vegetable consumption against the risks for insulin resistance and hypertension, in part due to the potassium and fibre contributions of these foods, 22 making it a vital component of the diet in the treatment of T2DM. Causes of the low intakes of these foods were not assessed in the current study, but may be related to poverty, seasonality or inaccessibility of fresh fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…However, a satisfactory understanding of weight measurement techniques was found in patients from Ghana [15]. The majority of our patients knew that increased calorie intake (264 [63.3%]) and lack of exercise (260 [62.4%]) were risk factors for obesity, as also shown by studies carried out in Bangladesh [12], Ghana [15], and South Africa [16].…”
Section: Discussionsupporting
confidence: 54%
“…Worldwide fatality and disability rate' enforced diabetic patients to Insulin self-administration despite a scarcity of their Knowledge, Attitude, and Practices. [1][2][3][4][5] The good knowledge, favorable attitude, and practices of insulin self-administration (ISA) among insulated diabetic patients including taking medication properly, regular exercise, following a diabetic meal plan, and blood glucose test are some of the most crucial components' glycemic control. 2,3 Worldwide, the prevalence of good knowledge and favorable attitudes ISA was ranged nearly from 33.3% to 98.7%, 50.3% to 98% receptively.…”
Section: Introductionmentioning
confidence: 99%
“…3 In South Africa, a result reveals that there is Poor knowledge, a negative attitude, and poor practices related to diabetes were observed which uncover morbidity and death. 4 Lack of understanding of patients' characteristics and diabetesrelated knowledge, practice, and attitude will lead to a high possibility of unsuitable direction and faulty education program. [5][6][7][8] Research studies conducted in different parts of the world showed evidence of inadequate knowledge and poor practice level on ISA among DM patients.…”
Section: Introductionmentioning
confidence: 99%